Quality of the health care network: evaluation by the patient with Diabetes Mellitus - Nayara R. Baldoni; Claudia L. Oliveira; Alex M. Neves; Bruno M. Silva; Carolina S. Penha; Gilson S. Santos; Marcella L. Duarte; Samuel B. Santos; Clareci S. Cardoso (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2019)
Introduction: Diabetes Mellitus (DM) is a common chronic condition that needs an organized and qualified health care network to provide appropriate prevention and treatment of this condition. These investigation mains to assess the quality of health care network according to the perception of patients diagnosed with DM. Method: It was conducted a cross-sectional study inside a cohort follow-up. Primary health care users were interviewed to evaluate quality of the health care network using the Patient Assessment of Care for Chronic Conditions scale. Clinical and socio demographic information was collected. Results: A total of 24 patients was interviewed, and the overall score of scale was 2.25 (1-5). When the patients were classified by groups based on the control of the DM, the overall score for those with controlled diabetes was lower (2.11) than the group of participants with not controlled diabetes (2.66). Discussion: It was found a low global evaluation of the health care network by the patients. This finding can be related with a low health literacy by the patients included in this evaluation. Conclusion: The lack of a health care network for chronic conditions acting in a coordinated care can compromised the quality of care provided to DM patients, as noted by the low overall scores of evaluations. A more positive assessment among patients not controlled in their glycemic level may reflect an incipient health literacy these patients.